Voltage instability detection using synchrophasor measurements: A review. (2nd March 2020) - Chappa, Hemanthakumar; Thakur, Tripta
Summary: This article presents the concept of voltage instability and a critical review of the literature available for detecting voltage instability in the power system. Initially, the problem of voltage instability, the signification of P‐V, Q‐V curves, the effect of load models, on‐load tap changer (OLTC), and over‐excitation limits of generators on voltage instability are lucidly explained. A very brief description of conventional methodologies for voltage instability detection is also presented. This literature review mainly focuses on methodologies based on synchrophasor measurements including both local and global measurements. These methodologies' feasibility for real‐time application has been investigated. The indices that are compared for instability detection may serve as an introduction to measurement‐based voltage instability detection methodologies. The measurement‐based indices that are analyzed and compared are mainly based on the concept of Thevenin parameters estimation, generator equivalent models, nodal reactive power loss concept, and apparent power difference criteria. Thus, this paper attempted to compile all the work reported so far for voltage instability detection using synchrophasor measurements and for each methodology merits and demerits are lucidly discussed and are tabulated.